1998
DOI: 10.1590/s0074-02761998000200002
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Frequency and Feeding Habits in an Enzootic Canine Dirofilariasis Area in Niterói, State of Rio de Janeiro, Brazil

Abstract: Heartworm, a chronic fatal mosquito-borne canine disease, is frequently diagnosed in dogs from the State of Rio de Janeiro, where its prevalence is 29.7% in the city of Niterói. Nevertheless it is rarely detected in cats (0.8%) from the same state. Dogs are the primary source of infection to mosquitoes, because cats either do not demonstrate microfilaremia or it is too low and transient for transmission. A mosquito survey was conducted in Itacoatiara, Niterói, from March 1995 to February 1996, using canine, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
10

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 22 publications
(17 reference statements)
1
20
0
10
Order By: Relevance
“…Nonetheless, the climate conditions in Brazil are so suitable that a range of arthropod vectors are found the year-round. For instance, studies carried out in an area of D. immitis endemicity in Rio de Janeiro indicated that mosquito vectors (e.g., Ochlerotatus scapularis and Ochlerotatus taeniorhynchus ) are more abundant during summer months, but may also be captured in high number in winter months [174]. These findings suggest that dogs and cats may be at risk of D. immitis infestation during the whole year, especially because the average annual temperature in most of the Brazilian territory is between 21 and 30°C, which indeed facilitates the development of infective larvae (L3) in the mosquito vector.…”
Section: Reviewmentioning
confidence: 99%
“…Nonetheless, the climate conditions in Brazil are so suitable that a range of arthropod vectors are found the year-round. For instance, studies carried out in an area of D. immitis endemicity in Rio de Janeiro indicated that mosquito vectors (e.g., Ochlerotatus scapularis and Ochlerotatus taeniorhynchus ) are more abundant during summer months, but may also be captured in high number in winter months [174]. These findings suggest that dogs and cats may be at risk of D. immitis infestation during the whole year, especially because the average annual temperature in most of the Brazilian territory is between 21 and 30°C, which indeed facilitates the development of infective larvae (L3) in the mosquito vector.…”
Section: Reviewmentioning
confidence: 99%
“…Data on the collection sites and methods are available in Labarthe et al (1998). Briefly, mosquitoes were captured four days each month using a dog, a cat and two human volunteers as baits, from March 1995until February 1996 Mosquitoes were kept in cylindrical cages of 8.5 cm diameter at 28°C, 80% RH and provided with a 10% glucose solution.…”
Section: Methodsmentioning
confidence: 99%
“…caspius , Culiseta annulata , Ochlerotatus scapularis , Culex declarator and Cx. p. pipiens ) than cats [68,69]. In spite of this, cats are not good reservoirs for D. immitis , mainly due to host resistance, as inferred by the low adult worm burden in natural and experimental infections, the long prepatent period (8 months), the low level and short duration of microfilaraemia and life span of adult worms (2–3 years) in this host species [70].…”
Section: Reviewmentioning
confidence: 99%